Task-technology fit analysis of social media use for marketing in the tourism and hospitality industry: a systematic literature review. Issue 8 (16th July 2020) - Lin, Hsien-Cheng; Han, Xiao; Lyu, Tu; Ho, Wen-Hsien; Xu, Yunbao; Hsieh, Tien-Chih; Zhu, Lihua; Zhang, Liang
Abstract : Purpose: Research in tourism and hospitality industry marketing has identified many highly effective applications of social media. However, studies in the existing literature do not enable a comprehensive understanding of this phenomenon because they lack a theoretical foundation. Therefore, this study systematically reviewed the literature from the perspective of the task-technology fit (TTF) theory. The purpose of this paper is to map out what is known about social media use in tourism and hospitality marketing and what areas need further exploration. Design/methodology/approach: A descriptive cumulative review of the literature obtained 99 articles published in tourism and hospitality journals from 2010 to 2019. Findings: The analysis suggests that to understand social media use in tourism marketing, researchers and practitioners in the industry must clarify the following four issues: the control variables, longitudinal analyzes and TTF concepts that should be used in future studies; the fitness of social media platforms for tourism marketing; how various social media platforms differ in terms of performance outcome; and the digital divide in the use of social media for tourism. Originality/value: An integrated framework was developed to identify constructs and to understand their relationships. Recent studies in this domain are discussed; theoretical and practical suggestions and implications for future research are given.